Reduction in Albumin-Creatinine Ratio Following Integrative Ayurvedic Care in Elderly Woman with Type 2 Diabetes and MASLD: A Case Report - Aman Singhal; Shivani Ghildiyal; Vanshika Sharma; Vaidehi Dutt (Indian Journal of Health Sciences and Biomedical Research KLEU, 2026)
Background: Metabolic dysfunction–associated steatotic liver disease (MASLD) frequently coexists with type 2 diabetes mellitus (T2DM) and early diabetic kidney disease, and the combination accelerates both hepatic and renal risk. Conventional care is centred on glycaemic and lipid control and renin–angiotensin blockade, but residual symptom burden and incomplete biomarker control are common, prompting interest in adjunctive whole-system approaches.Case presentation: An elderly woman aged 70 years with recently detected T2DM, long-standing nephrolithiasis and dyslipidaemia presented to an Ayurvedic hospital with anorexia, bilateral hypochondrial pain after meals, acidity and headache. Baseline evaluation (July 2025) showed HbA1c 7.5%, LDL-cholesterol 184 mg/dL, total cholesterol 263 mg/dL, urine albumin–creatinine ratio (ACR) 47.27 mg/g (category A2), preserved eGFR (94 mL/min/1.73 m2), and ultrasonographic grade-II hepatic steatosis with bilateral medical renal disease, non-obstructive calculi and nephrocalcinosis.Intervention: Alongside continuation of metformin and an oral hypoglycaemic/lipid regimen prescribed elsewhere, the patient received individualised classical Ayurvedic formulations (including Varunadi and Vasaguluchyadi kvatha, Gokshuradi guggulu, Avipattikara churna, Arogyavardhini vati, and proprietary hepato-renal preparations M-Liv and Neeri-KFT) over approximately five months, with dietary and hydration advice.Outcome: By December 2025 the patient reported symptomatic improvement, and repeat urine ACR had fallen from 47.27 to 20.62 mg/g (re-classification from A2 to A1). Serum creatinine remained normal. No adverse event was documented. Causality cannot be inferred from a single uncontrolled case.Conclusion: In this individual patient, integrative Ayurvedic care administered as an adjunct to conventional therapy was associated with symptomatic improvement and a measured reduction in albuminuria over five months. Controlled prospective studies are required before any therapeutic claim can be made.